Effect of ISO 9001:2015 Quality Management Implementation in Education on School Performance - Parso; Pujiati, Herni; Bagaskoro; Sunarsi, Denok; Yusnaldi; Nurjaya; Affandi, Azhar; Anggraeni, Noerlina (The journal of contemporary issues in business and government, 2021)
The purpose of this study was to determine the impact of implementing ISO 9001: 2015 on school performance as measured by the Balanced Scorecard. Primary data were obtained by distributing questionnaires to 120 respondents who were teachers and school employees in Tangerang. The independent variable in this study is the application of the principles of ISO 9001: 2015 while the dependent variable is good school performance from a perspective finance, customer perspective, internal business perspective, and learning and growth perspective. To determine the effect of independent variables and dependent variables, path analysis method is used. The results of data processing show that there is a positive influence between the application of ISO 9001: 2015 on school performance from a financial perspective, a customer perspective, an internal business perspective, and a learning and growth perspective. From these results the authors suggest that other agencies apply the principles of ISO 9001: 2015 in the management of their institutions to improve their performance.